Type i endoleak management after endovascular repair of infrarenal abdominal aortic aneurysm: Utilization of n-butyl cyanoacrylate embolization in a case of failed secondary intervention - (:unkn) unknown (HMP Communications, 2014)
A 52-year-old male patient with an infrarenal abdominal aortic aneurysm underwent an endovascular aneurysm repair procedure. At the end of the procedure, a type 1A endoleak was detected. Because there was no margin for placement of an aortic extender cuff, balloon dilatation was performed with an expectation for total resolution. A control angiogram performed 2 days later showed that the endoleak persisted and balloon dilatation was performed at the attachment site one more time. A control CT scan performed 2 days after the secondary procedure revealed that the type IA endoleak persisted and had grown larger. Open surgical repair was rejected by the patient. The patient underwent a single session of N-butyl cyanoacrylate embolization of the type IA endoleak using a transarterial approach. Coil utilization was not required. Technical success was achieved in the patient with complete resolution of the endoleak confirmed by follow-up CT studies. There were no procedure-related complications.
Keywords: abdominal aortic aneurysm; aortic aneurysm stent graft; embolization; endoleak; endovascular aneurysm repair; endovascular therapy; graft intervention; interventional radiology; N-butyl cyanoacrylate